The necessity for an ethnographic approach in Peru - Cometti, G (Refugee Studies Centre, University of Oxford, 2015)
A movement of people is rarely explained by environmental or climatic factors alone. Therefore an analysis which does not take into consideration the cultural consequences of climate change for affected societies is incomplete.